MENGUJI FAKTOR YANG MENJADI DETERMINAN BAGI EARNING RESPONSE COEFFICIENT PADA PERUSAHAAN REAL ESTATE DAN PROPERTI DI INDONESIA - Muhammad Rizal Saragih; Rusdi Rusdi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Investors' assessment of the company is very influential on the company's progress, especially the market response. Therefore, considering earnings as keywords must be a priority, this is a challenge for the company. In this study will present a study of earning response coefficient and the factors that actually affect, property sector as an object of research. The sample of this study were 24 Real Estate and Property companies listed on the Indonesia Stock Exchange, with a quantitative approach. The results showed that CSR was the only predictor. This explains that the company's social activities assume that the company has a large profit potential, why? because social activities can only be done if the company has profits, more and more CSR activities being held shows the company has a large profit. Keywords: Corporate Social Responsibilty, Price To Book Value, Audit Firm Reputation, Earning Response Coefficient